Aortic valve replacement after previous TAVI - D. A. Titov; M. N. Sorkomov; D. M. Pursanova; M. I. Fedoseykina; S. I. Babenko; R. M. Muratov (Вестник трансплантологии и искусственных органов, 2023)
Endovascular surgery for aortic valve defects has proven itself well in elderly patients with severe comorbidities competing with the underlying disease. However, the risk of dysfunction resulting from structural degeneration of bioprosthetic heart valve and prosthetic valve endocarditis remains high. Repeated surgeries are associated with complications, but open surgery is the only method of treatment in this group of patients.Objective: to describe a series of reinterventions for prosthetic valve dysfunction occurring after TAVI.Material and methods. From 2015 to 2022, at the Department of Emergency Surgery for Acquired Heart Diseases (Head, Professor R.M. Muratov), Bakulev Research Center for Cardiovascular Surgery, 6 reoperations were performed in patients who had previously undergone transcatheter aortic valve implantation (TAVI). The average age of patients at the time of TAVI and at the time of reoperation was 70.6 years (62–83) and 74.3 years (70–84), respectively. The EuroSCORE II predicted risk of mortality at the time of reintervention was 42.2% (21.7–87.6). The mean time to reoperation was 42 months. Indications for reoperation were early active prosthetic endocarditis (4 cases) and structural valve degeneration (2 cases).Results. At the hospital stage, 1 patient died of acute heart failure; the operation was performed for vital indications in conditions of extreme initial severity. In three patients, the early postoperative period was uneventful. One patient required intra-aortic balloon counterpulsation (IABP) due to heart failure, and 1 patient was implanted with permanent pacemaker. The average time of hospitalization was 14 days. Patients with active prosthetic endocarditis received a 6-week course of antibiotic therapy. The function of the implanted valves was satisfactory.Conclusions. Aortic valve replacement after previous TAVI is an emergency operation and represents the only way to treat valve dysfunction. Under active prosthetic endocarditis, timely surgery can save this patient cohort.